Carbapenem-resistant Acinetobacter baumannii (CRAB) Recovered from Burn Patients - Adibhesami, Habibeh; Douraghi, Masoumeh; Zeraati, Hojjat; Bazmi, Fariba; Rahbar, Mohammad; Pourmand, Mohammad Reza; Tabrizi, Mahboobeh Satarzadeh; Aliramezani, Amir; Ghourchian, Sedigheh (Journal of Pharmacy & Pharmaceutical Sciences, 2016)
Purpose. Emergence of carbapenem-resistant Acinetobacter baumannii (CRAB) and their prolonged presence in burn units increases the risk of acquisition of CRAB. Methods. From November 2012 to September 2013, 1474 burn patients were screened for CRAB isolates through testing susceptibility to imipenem and its comparators meropenem, and doripenem. Furthermore, the in vitro activity of other antibiotics against CRAB was investigated. Results. Three patients were infected with carbapenem-susceptible A. baumannii (CSAB) and 168 were infected with CRAB. Approximately one-fifth (n=32) of CRAB isolates were obtained from patients hospitalized in Burn Intensive Care Unit (BICU). Most of CRABs were isolated from wound. The mean length of stay (LOS) in hospital prior to A. baumannii isolation was significantly higher for CRAB compared to CSAB cases (P=0.04). Amongst the independent variables, percentage of total burn surface area (TBSA) significantly increased the mortality rate using multivariate logistic regression (P=0.001, OR= 16.5; 95% CI: 4.72-57.7). The majority of tested isolates were resistant to imipenem (94.8%), and to its comparators, doripenem (97.7%), and meropenem (97.7%). The susceptibility of CRAB isolates was less than 10% to all tested antibiotics except for colistin (100%), doxycycline (61.9%), gentamicin (18.5%), and tigecycline (11.9%). Conclusion. Resistance to carbapenem reduces the number of effective antibiotics. The coordinated and intensive efforts of healthcare personnel are required to meet the challenge of dissemination of CRAB.